The scope of application of additive technologies by the method of plasma surfacing in the manufacture of aircraft engines - Konstantin Balushok; Sergey Chigileychik (Авіаційно-космічна техніка та технологія)
The determination of the scope of application of additive technologies by the method of plasma surfacing in the manufacture of aircraft engines is determined by ensuring the mechanical and service properties of heat-resistant nickel and titanium alloys during the production of blanks, necessary for the operation and determination of the technological capabilities of this method. To determine the mechanical properties, 140×70×14 mm heat-resistant nickel alloys ЭП 648ВИ, ВЖ 98ВИ and titanium alloys ВТ6, ВТ20 were grown. After growing, all samples underwent heat treatment according to the technical conditions for each alloy. The mechanical properties for ЭП 648ВИ were determined on these samples (transverse direction: σВ=83.5 kgf/mm2; σ0.2= 63.5 kgf/mm2; δ= 11.2 %; ψ = 21.8 %; longitudinal direction: σB=87.5 kgf/mm2; σ0.2= 57.3 kgf/mm2; δ=21.8 %; ψ= 23.5 %), for ВЖ98 (transverse direction: σВ=83.5 kgf/mm2; σ0.2= 63.5 kgf/mm2; δ= 11.2 %; ψ= 21.8 %, longitudinal direction: σВ=87.5 kgf/mm2; σ0.2= 57.3 kgf/mm2; δ=21.8 %; ψ= 23.5 %), for ВТ6 (transverse direction: σВ=92.2 kgf/mm2 σ0.2= 84.8 kgf/mm2; δ= 17.2 %; ψ= 54.3 %; longitudinal direction: σВ=98.9 кгс/мм2; σ0.2= 91.0 кгс/мм2; δ=9.8 %; ψ= 22.5 %), for ВТ20 (transverse direction: σВ= 115 kgf/mm2; σ0.2= 108 kgf/mm2; δ=15 %; ψ=29.3 %; longitudinal direction: σВ=114 kgf/mm2; σ0.2= 103 kgf/mm2; δ= 14.0 %; ψ=37.6 %). The obtained properties of heat-resistant nickel and titanium alloys are not inferior to blanks obtained by casting and forging methods. The scope of application of additive technologies by the method of plasma surfacing in the manufacture of aircraft engines is defined. For heat-resistant nickel alloys, these are parts included in nozzle devices, heat pipes and combustion chambers. For titanium alloys, these are parts included in the body. From the technological possibilities, the plasma surfacing method is most rationally used when growing cylindrical and conical workpieces of parts with a diameter of 150 to 1500 mm. The technology of adaptive plasma cultivation has been introduced into serial production at JSC "Motor Sich". Currently, more than 20 different types of aircraft engine parts are being produced.